HUBUNGAN MOTIVASI BELAJAR DENGAN KREATIVITAS BELAJAR PESERTA PELATIHAN MENJAHIT DI UPTD BLK ( BALAI LATIHAN KERJA) KECAMATAN TANAH LILI KABUPATEN LUWU UATARA - Muhaemin B Muhaemin B; Asri Muhammad (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2024)
This research aims to: Find out the learning motivation of sewing training participants, the learning creativity of sewing training participants and the relationship between learning motivation and learning creativity of sewing training participants at the UPTD BLK (Work Training Center) Tana Lili District, North Luwu Regency. This type of research is quantitative research using correlational data analysis techniques. The independent variable  in this research is learning motivation, while the dependent variable in this research is learning creativity. The population in this study was all sewing training participants at the BLK, Tana Lili District, North Luwu Regency, totaling 30 people. In this study, no samples were drawn because it was a population study. The data collection method was carried out using instruments in the form of questionnaires and documentation. The data analysis technique used is product moment correlation. The research results show that: 1) The learning motivation of sewing training participants is in the good category. 2) The learning creativity of sewing training participants is in the good category. 3) there is a positive and significant relationship between learning motivation and learning creativity of sewing training participants at the UPTD BLK (Job Training Center) Tana Lili District, North Luwu Regency.